The Existence of Classical Malay Literature in the Era of Industrial Revolution 4.0 - Effendy, Chairil; Muhammad, Asrori (Advances in Social Sciences Research Journal, 2024)
This study aims to investigate the structure of Syair Gulung that are still being created, the materials, themes, the publics’ acceptance and the effectiveness of syair gulung. The Syair Gulung were studied from three books, namely Syair Bunga Jambu, Syair Gulung Ketapang and Kumpulan Naskah Lomba Syair Gulung. The heuristic and hermeneutic reading methods were used in this study. The findings indicate that the structure of Syair Gulung was relatively similar to the hundred-years-old general verse pattern: the opening and closing stanzas were formulaic, consisting of four words, rhyming a-a-a-a. Some of the materials that were processed into poetry came from folklore and some from daily social activities. The themes of Syair Gulung were related to love, greed, preservation of Malay culture, love for Islam and the Prophet of Muhammad as well as effort to create and maintain the harmonization of the nation and state. At the same time, given the fact that until present, Syair Gulung are still being created and sung on various occasions, even being contested among students and the general public. It can interpreted that Syair Gulung are still effective in carrying out the function as a medium for conveying certain messages.